The Forgiveness to Come : the Holocaust and the Hyper-Ethical. - Banki, Peter Jason (Just Ideas Ser., 2017)
Examines the debate on forgiveness in relation to the Holocaust. Discusses Simon Wiesenthal's The Sunflower, Jean Ame#65533;ry's At the Mind's Limits, Vladimir Janke#65533;le#65533;vitch's Forgiveness, Robert Antelme's The Human Race and Forgiving Doctor Mengele on Eva Mozes Kor in the light of Jacques Derrida's concept of forgiveness of the unforgivable.